Building Fire Risk Assessment Jatinegara District Health Center East Jakarta - Dliya Aulia Rahman (Politeknik Siber Cerdika Internasional, 2023)
Public health center Subdistrict Jatinegara potential experience fire building because exists activities that can cause fire building , such as use fires in laboratories and kitchens as well as use of B3 with properties easy ignite or explode in parts generator maintenance . This research aims to find out evaluation risk fire building Public health center Subdistrict Jatinegara East Jakarta 2022 with an identification process danger , identification risk , analysis risk and evaluation risk . Evaluation risk fire carried out at the Community Health Center Subdistrict Jatinegara in September-December 2022 using qualitative methods referring to AS/NZS 4360 of 2004. From the identification results danger is known that source the dangers that exist in the health center Subdistrict Jatinegara originate from tools and auxiliary materials Work as well as work processes . From the identification results risks with the JSA form are known that danger the risky cause wound burnt , deformed still until death . From the results of the analysis risk obtained conclusion that level risk fire at the health center Subdistrict Jatinegara are in the risk category extreme , and after done evaluation risk , the results obtained are: risk fire at the health center Subdistrict Jatinegara is very high or in the red zone and can be concluded that unacceptable risk . The researcher 's suggestion to give is to control the dangers that exist in the health center Subdistrict Jatinegara needs a hierarchy of control, routine do simulation fire involving all elements in the Puskesmas Subdistrict Jatinegara and routine do supervision to system protection existing fire